Optimization of Biodegradation Characteristics of Sphingopyxis sp. YF1 against Crude Microcystin-LR Using Response Surface Methodology - Isaac Yaw Massey; Tangjian Peng; Cai Danping; Fei Yang (Toxins, 2022)
Sphingopyxis sp. YF1 has proven to be efficient in biodegrading microcystin (MC)-leucine (L) and arginine (R) (MC-LR); however, the optimal environmental factors to biodegrade the toxin have not been investigated. In this study, the biodegrading characteristics of strain YF1 against MC-LR were assessed under diverse environmental factors, including temperature (20, 30 or 40 °C), pH (5, 7 or 9) and MC-LR concentration (1, 3 or 5 µg/mL). Data obtained from the single-factor experiment indicated that MC-LR biodegradation by strain YF1 was temperature-, pH- and MC-LR-concentration-dependent, and the maximal biodegradation rate occurred at 5 µg/mL/h. Proposing Box-Behnken Design in response surface methodology, the influence of the three environmental factors on the biodegradation efficiency of MC-LR using strain YF1 was determined. A 17-run experiment was generated and carried out, including five replications performed at the center point. The ANOVA analysis demonstrated that the model was significant, and the model prediction of MC-LR biodegradation was also validated with the experimental data. The quadratic statistical model was established to predict the interactive effects of the environmental factors on MC-LR biodegradation efficiency and to optimize the controlling parameters. The optimal conditions for MC-LR biodegradation were observed at 30 °C, pH 7 and 3 µg/mL MC-LR, with a biodegradation efficiency of 100% after 60 min. The determination of the optimal environmental factors will help to unveil the detailed biodegradation mechanism of MC-LR by strain YF1 and to apply it into the practice of eliminating MC-LR from the environment.